دراسة تأثير خلطات مختلفة من أوساط النمو في نمو شتول الفليفلة وتحملها صدمة التشتيل (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
This research work aimed to study the effect of different mixtures of growing media on pepper seedlings and their ability to withstand transplanting shock.The variety QarnAlgazal of pepper and five mixtures of growing media were used.The mixtures included bitmoss alone,bitmoss with equal volume of soil or sand,soil and cow manure in a ratio of 1:2,and cow manure with soil and sand in a ratio of 1:1:1.The experiments were implemented in aplastic green house without heating in the nursery farm of the faculty of Agriculture,Tishreen University.The completely randomizel design was adopted with three replications for each treatment and 15 plants for each replication.The results showed that themedia containing cow manurewere the more effective ingrowth of sapling as represteded by the increased hieght of sapling, number and area of leafs,fresh weight of both biomass and roots of sapling.The effect was very clear in the media containing cow manure and soil in the ratio of 1:2.هدف البحث إلى دراسة تأثير خلطات عدة من أوساط النمو في نمو شتول الفليفلة، وفي مقدرتها على تحمل صدمة التشتيل.استخدم من أجل ذلك الصنف البلدي "قرن الغزال" من الفليفلة، وخمسة أوساط تختلف في نسب مكوناتها الحجمية،اشتملت على البيت– موس منفرداً, كما استخدم خلطتين مؤلفتين من وحدات حجمية متساوية من البيت–موس, وعلى كل من التراب أوالرمل, وخلطة واحدة من التراب والزبل البقري بنسبة ، وخلطة من الزبل البقري المتخمر، والتراب، والرمل بنسبة 1:1:1.نفذت التجارب في بيت بلاستيكي غير مدفأ في المشتل الزراعي التابع لكلية الزراعة بجامعة تشرين على وفق التصميم العشوائي الكامل, بثلاثة مكررات للمعاملة الواحدة، وبمعدل خمسة عشر نباتاً للمكرر الواحد.أظهرت النتائج أن الأوساط المحتوية على الزبل البقري المتخمر هي الأكثر تأثيراً في نمو الشتول، وتمثل ذلك بزيادة أطوال الشتول، وأعداد الأوراق، وبمساحة مسطحها الورقي، وكذلك في زيادة الوزن الرطب للمجموعين الخضري والجذري للشتول، وكان هذا الدور أكثر وضوحاً في الوسط المحتوي على التراب و الزبل البقري المتخمر بنسبة 2:1.